Biotransformation and genotoxic biomarkers in mullet species (Liza sp.) from a contaminated coastal lagoon (Ria de Aveiro, Portugal) - Pacheco, M. (2005)
The aim of the present study was to assess liver ethoxyresorufin-O-deethylase (EROD) activity and erythrocytic nuclear abnormalities (ENA) frequency in three mullet species, as biotransformation and genotoxicity biomarkers, respectively, for monitoring aquatic ecosystems. Specimens of Liza aurata, Liza ramada and Liza saliens were caught bimonthly, between May 2000 and March 2001, at nine stations in the Ria de Aveiro (Portugal), a polluted coastal lagoon. The survey revealed two critical areas (Vagos and Carregal) where it was observed elevated EROD activity and ENA frequency, comparing to the reference sites. The results often reflect a contamination by a mixture of pollutants, from point and non-point sources. Nevertheless, the responses observed at Vagos are probably attributable to high polycyclic aromatic hydrocarbon (PAH) water levels measured at that station. All species were able to detect inter-site differences; however L. aurata seems to be the most appropriate bio-indicator due to its larger geographical distribution and abundance during the whole year. The adopted biomarkers, applied to mullet species, can be successfully employed for biomonitoring anthropogenic contamination in both Atlantic and Mediterranean European coastal waters.